Tuning the formation of reductive species of perylene-bisimide derivatives in DMF via aggregation matter - Kang, Rui; Miao, Rong; Qi, Yanyu; Chang, Xingmao; Shang, Congdi; Wang, Li; Fang, Yu (Chemical communications (Cambridge, England), 2017)
Host-guest interaction and chemical modification are found to be effective in tuning the formation of reductive species of perylene-bisimide (PBI) derivatives in DMF. Moreover, some of the PBI derivatives as synthesized produce radical anions in the solvent without the need of a base.